Why do Firms reimburse Job Applicants' Relocation Costs? - Jos van Ommeren; Piet Rietveld (Tinbergen Institute, 2002)
We develop an equilibrium job search model in which employees incur commuting costs, and residential relocation is costly. We demonstrate that firms partially compensate workers for the incurred relocation costs to avoid paying compensation for commuting costs.
Keywords: 330; Wohnungswechsel; Suchtheorie; Betriebliche Sozialleistungen; Theorie; Pendelverkehr